Implementasi Arsitektur Microservices Menggunakan RESTful API Untuk Website Online Course Esploor - Fath, Tata Redha Al; Amin, Imam Husni Al (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Rapid technological developments affect various aspects of life, such as education. Many online learning platforms provide various materials needed by the community. Online course applications usually consist of many interconnected services. Traditionally, applications are built with a monolithic approach that makes all services in the same codebase, so they often experience many problems as the system grows larger. The online course application will be created using a microservices architecture to facilitate maintenance and update. Microservices are intended so that each service can perform one function well. One service with another service can be connected using the Application Programming Interface (API) such as REST. The system design uses the Web Service Implementation Methodology (WSIM). This online course application uses two languages, JavaScript and PHP on the BackEnd side and MySQL as a Database Management System (DBMS) to store data and ReactJs technology to build a user interface.